2009
DOI: 10.1088/0169-5983/42/2/025508
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental verification of a theoretical model of ripple formation in ice growth under supercooled water film flow

Abstract: Abstract. Little is known about morphological instability of a solidification front during the crystal growth of a thin film of flowing supercooled liquid with a free surface: for example, the ring-like ripples on the surface of icicles. The length scale of the ripples is nearly 1 cm. Two theoretical models for the ripple formation mechanism have been proposed. However, these models lead to quite different results because of differences in the boundary conditions at the solid-liquid interface and liquid-air su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(105 citation statements)
references
References 24 publications
(127 reference statements)
6
97
2
Order By: Relevance
“…Past theoretical works have explained the formation of icicles by pure water falling films (e.g. Ueno et al 2010), but the recent experimental findings by Chen & Morris (2013) have questioned whether pure water is able to trigger icicle formation. The experiments in fact required the presence of dissolved salts in order to see appreciable instabilities.…”
Section: The Stokes Model: Analytical Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past theoretical works have explained the formation of icicles by pure water falling films (e.g. Ueno et al 2010), but the recent experimental findings by Chen & Morris (2013) have questioned whether pure water is able to trigger icicle formation. The experiments in fact required the presence of dissolved salts in order to see appreciable instabilities.…”
Section: The Stokes Model: Analytical Solutionmentioning
confidence: 99%
“…When coupled to heat conservation equations and an interface evolution law (i.e. the Stefan condition), this equation allowed the stability analysis of icicles (Ueno et al 2010) and ice ripples (Camporeale & Ridolfi 2012b) to be developed theoretically. Some doubts have been raised by Chen & Morris (2013) on the validity of the former theory that we will comment on later, in § 3.4.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, upward ripple motion at about half speed of the mean growth rate of icicle radius was observed experimentally as theoretically predicted, but downward traveling ripples were not observed. 7 In the previous theoretical models, [3][4][5][6][7] ice was covered with a supercooled water layer and there was no airflow around icicles. The latent heat released at the ice-water interface was assumed to be transferred in the air by thermal diffusion through the water layer.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] A stability analysis for the ice-water interface disturbance was developed based on heat flow in the water and atmosphere, and thin film water flow dynamics. From the initial model, it was found that the ripple wavelength is determined from =2h 0 Pe l / ␣ max , and that the ripples should move down the icicle.…”
Section: Introductionmentioning
confidence: 99%
“…Icicles are stalactites, where ripples decorate the surface as for their limestone analogue (Fig. 4.17b and Ueno et al, 2010). Spectacular dissolution scallops form on the walls of melt water tunnels in glaciers, just as in the analogous karst setting, and rillenkarst is a familiar sight on melting glaciers and ice cubes in drinks (Fig.…”
Section: A Cold Note On Universality: Bringing It All Togethermentioning
confidence: 99%